Immobilization of metallothionein to carbon paste electrode surface via anti-MT antibodies and its use for biosensing of silver - Trnkova, Libuse; Krizkova, Sona; Adam, Vojtech; Hubalek, Jaromir; Kizek, Rene (Biosensors & bioelectronics, 2011)
In this paper, heavy metal biosensor based on immobilization of metallothionein (MT) to the surface of carbon paste electrode (CPE) via anti-MT-antibodies is reported. First, the evaluation of MT electroactivity was done. The attention was focused on the capturing of MT to the CPE surface. Antibodies incorporated and mixed into carbon paste were stable; even after two weeks the observed changes in signal height were lower than 5%. Further, the interaction of MT with polyclonal chicken antibodies incorporated in carbon paste electrode was determined by square-wave voltammetry. In the voltammogram, two signals--labelled as cys(MT) and W(a)--were observed. The cys(MT) corresponded to -SH moieties of MT and W(a) corresponded to tryptophan residues of chicken antibodies. Time of interaction (300 s) and MT concentration (125 μg/ml) were optimized to suggest a silver(I) ions biosensor. Biosensor (CPE modified with anti-MT antibody) prepared under the optimized conditions was then used for silver(I) ions detection. The detection limit (3 S/N) for silver(I) ions was estimated as 0.5 nM. The proposed biosensor was tested by detection spiking of silver(I) ions in various water samples (from very pure distilled water to rainwater). Recoveries varied from 74 to 104%.
Keywords: metalothionein; konduktometrie; Equipment Design; Immunoassay; Metallothionein; analýza selhání vybavení; Silver; povrchové vlastnosti; vazba proteinů; Antibodies; Equipment Failure Analysis; Biosensing Techniques; Conductometry; Electrodes; imunoanalýza; biosenzitivní techniky; elektrody; design vybavení; Carbon; uhlík; Surface Properties; Protein Binding; stříbro; protilátky